From simple questions to complex issues, IDNLearn.com has the answers you need. Ask any question and receive comprehensive, well-informed responses from our dedicated team of experts.
Answer:
here is a simple version
lets make A equal the exponent so (A=^2 or 3 or whatever)
the exponent will be the amount of times you want to repeat the process.
Now lets make x = the first array, so x=3
and lets make y = the second array, y=7
now a simple equation would be (3x)(7y)^A or for this you could say
(3x)(7y)^6